PENGARUH PEMBERIAN EDUKASI MELALUI VIDEO TERHADAP KESIAPAN PULANG PASIEN DENGAN PENYAKIT JANTUNG KORONER DI RUMAH SAKIT DAERAH (RSD) MANGUSADA BADUNG - Dewi, Ni Luh Suari Sasmita; Susila, I Made Dwie Pradnya; Purwaningsih, Ni Komang (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Health education is defined as the process by which health professionals provide information to patients that will change their health behavior or improve their health status. Properly targeted health education can lead to reduce hospitalizations. Educational interventions in heart care have been shown to increase physical activity and lead to healthy dietary habits and smoking cessation. One of the promotional methods that can be used to prepare home readiness of patients is audio visual media. This study aimed at determining the effect of video education on home readiness of patients with coronary heart disease in Mangusada Badung Regional Hospital. This study was a quasi-experimental study with a nonequivalent control group design. Home readiness of patients was analyzed using RHDS questionnaire. The control group (conventional lecture method) in this study was a group without video education, the treatment group had been given video education with 36 samples of each group using a systematic sampling method. Data analysis used t paired sample test and Man Whitney test. Based on Mann-Whitney U test with a confidence level of 95%, the results obtained P-value, = 0.000 with Z value = -7.215 therefore it can be concluded that providing video education media had a greater effect than providing lecture media education on home readiness of patients with coronary heart disease.